Mar233
Rozwiązane

Zad.5 Oblicz wartość liczbową wyrażenia
A) 2(x^2 - 2x + 3) -(x^2 - 3x - 1) dla x= 1/3

B) 4(5y+1)(1-5y) - 5(4x+1)(1 -4x) dla x= -1 i y=0.1​



Odpowiedź :

Odpowiedź:

A.

[tex]x=\frac{1}{3} \\\\ 2(x^{2} -2x+3)-(x^{2} -3x-1)=2x^{2} -4x+6-x^{2} +3x+1=\\ =x^{2} -x+7=(\frac{1}{3})^{2} -\frac{1}{3}+7=\frac{1}{9}-\frac{3}{9}+7=-\frac{2}{9}+7=6\frac{7}{9}[/tex]

B.

[tex]x=-1\\ y=0,1\\ \\ 4(5y+1)(1-5y)-5(4x+1)(1-4x)=\\ =4(1+5y)(1-5y)-5(1+4x)(1-4x)=\\ 4(1-25y^{2} )-5(1-16x^{2} )=4-100y^{2} -5+80x^{2} =\\ =4-100*(0,1)^{2}-5+80*(-1)^{2} =\\ =4-100*0,01-5+80*1=4-1 -5+80=78[/tex]

Odpowiedź:

Szczegółowe wyjaśnienie:

Zobacz obrazek Monikaczekol